Encouraging minority trust and compliance with police in a procedural justice experiment: How identity and situational context matter. (June 2023) - Murphy, Kristina
Poor police–minority relations have spurred calls for police reform worldwide. In response, scholars have suggested procedural justice as a way police might improve this relationship. This study explores how situational and person-specific factors condition how minorities interpret procedural justice in vicarious police encounters. The study adopts a randomized experiment with 504 Muslims. In the experiment, an officer's and Muslim suspect's behavior were both varied between groups in a police encounter. Participants' strength of identification with police was also measured. As expected, Muslim participants trusted the officer and complied more when the officer was depicted as procedurally just compared to procedurally unjust. However, this effect was moderated by the suspect's behavior; the procedural justice effect on trust was weaker when the Muslim suspect was depicted as disrespectful toward police. Identification with police also moderated the procedural justice effect on trust and compliance; the procedural justice effect was stronger for Muslims who identified more strongly with police. Finally, identification further moderated the Officer x Suspect Behavior interaction effect; the interaction was accentuated for those who identified more strongly with police. These findings suggest that procedural justice does promote minorities' trust in police and compliance, but situational and person-specific factors condition this.